(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
This article provides information on the importance of soybean from leguminous crops in increasing soil fertility. The "Genetic-1" soybean variety was used in the research. According to the results, these three types of soybeans are highly effective in increasing soil fertility.